2012
DOI: 10.1177/0011392112438340
|View full text |Cite
|
Sign up to set email alerts
|

Transforming health policy and services: Challenges for comparative research

Abstract: This paper presents different models that describe health determinants, services, and systems. It highlights the important model developed by Contandriopoulos, proposing a separation between the health status and health care circuits. The article is intended as a contribution to the field of comparative analysis with a new theoretical, methodological, and evaluative approach. Problems were identified in the development of a new model. Decentralization and access are introduced as categories, suggesting that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…As Burau [10], p. 569 highlights, more diverse comparisons have created ‘a range of challenges related to ensuring comparability, to comparing beyond the nation state, and to finding appropriate data for comparison’. Wrede [46] argues that case-based methods may help to capture complexity and, furthermore, highlights the benefits of interdisciplinary scholarship and methodological reflexivity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Burau [10], p. 569 highlights, more diverse comparisons have created ‘a range of challenges related to ensuring comparability, to comparing beyond the nation state, and to finding appropriate data for comparison’. Wrede [46] argues that case-based methods may help to capture complexity and, furthermore, highlights the benefits of interdisciplinary scholarship and methodological reflexivity.…”
Section: Methodsmentioning
confidence: 99%
“…Methodologically, we bring cross-country comparison to the meso-level of the organisation in a range of European countries. This brings a novel perspective into comparative research, because comparison traditionally focuses on institutions on the macro-level and often uses Anglo-American countries and/or National Health Service (NHS) systems as examples [10]. …”
Section: Introductionmentioning
confidence: 99%
“…These regard both health (1,2) and social care (3,4) systems, as well as informal care services (mainly provided by the family) traditionally available to support individuals in times of need (5). There is an increasingly variable relationship between supply and demand for services due to emerging factors like new health issues, such as the rise in chronic diseases and the increased chronicity of once incurable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to comparative case studies suggestion by the WHO is to look at available data with an aim to adapting it to a common unit of comparison [7]. Our proposed modifications to the Case Template can help to achieve this aim, and serves to address three identified challenges when engaging in service level comparisons across regional boundaries [16]:…”
Section: A Section Where Individuals Filling Out Templates Canmentioning
confidence: 99%
“…Comparative analyses focusing on health system reform have evolved over the last 20 years beginning with a macro level policy focus. More recent studies have focused on meso-level organizational processes and practices [16]. Comparative case studies at the organizational level have been shown to provide valuable insights with regard to effectiveness of interventions in particular contexts, can contribute to theory building, and can be used to guide implementation of new models [17].…”
mentioning
confidence: 99%